2013
DOI: 10.1089/sur.2012.108
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Surgical Site Infections in Abdominal Surgery: A Study in Nepal

Abstract: Surgical site infection is common among patients undergoing abdominal surgery at TUTH. This study identified some preventable risk factors associated with SSI at TUTH. Identification of such risk factors is expected to help surgeons improve patient care and decrease mortality and morbidity as well as the hospital-care cost of surgical patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 30 publications
6
41
1
Order By: Relevance
“…The risk ratio was also true when a braided was used. These findings are concordant with those in Nepal [ 2 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The risk ratio was also true when a braided was used. These findings are concordant with those in Nepal [ 2 ].…”
Section: Discussionsupporting
confidence: 92%
“…This contrasts with the overall SSI rate in mainland China which is at 4.5% [ 5 ] and that in Seoul, South Korea, at 3.3% [ 6 ] and that in the US at 2-3% [ 7 ]. In Ethiopia, SSI rates were found at 10.6% [ 8 ] whereas in a private hospital in Kenya incident rates of 7.0% were found [ 3 ] and the overall SSI rate in Nepal and Tanzania was 23% and 26%, respectively [ 2 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier prevalence studies have shown that Staphylococcus aureus and Pseudomonas aeruginosa were the most isolated organisms in post-operative wound infections accounting for 20–40% and 5–15% respectively [ 10 ], with the variation indicating geographical and temporal relationships [ 11 ]. Nosocomial infections and post-operative wound sepsis have remained a major cause of morbidity and death among the operated patients [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various authors have evaluated the incidence and risk factors for surgical site infection in surgical abdominal wounds. Giri S et al, 10 observed that out of 230 patients included, 53 were identified as having a SSI, resulting in an overall rate of SSI of 23%. Nwankwo E et al, 11 in their study observed that out of 2880 patients studied, 585 (20.3%) developed SSI.…”
Section: Prevalence Of Surgical Site Infectionmentioning
confidence: 99%